Ἀργὼ πᾶσι μέλουσα, παρ᾽ Αἰήταο πλέουσα – greckie źródła literackie do poznania mitu o Medei i wyprawie Argonautów po złote runo od VIII w. p.n.e. do III w. p.n.e. - Dworniak, Justyna (Studia Europaea Gnesnensia, 2019)
The myth of Medea and the Argonauts’ voyage to the faraway Colchis in search of the Golden Fleece belongs to the earliest legends of ancient Greece. The narrative elements of the tale would change over time. For almost thirteen centuries, from Homer to the late-antique poem Argonautica Orphica, which yet again retold the heroes’ expedition to Colchis, the legend of the Colchian sorceress and the fifty brave men fascinated ancient poets, historians and tragedians. Hence the paper focuses on the Greek literary sources which conveyed the tale. A detailed discussion of the works aims to highlight the diversity and multiplicity of the myth’s versions as well as outlines the evolution of the legend, whose most celebrated and recognized literary variant is found in Argonautica by Apollonius Rhodius.